Differential effects of parietal and frontal inactivations on reaction times distributions in a visual search task - Wardak, Claire; Ben Hamed, Suliann; Olivier, Etienne; Duhamel, Jean-René (Frontiers in Integrative Neuroscience, 2012)
The posterior parietal cortex participates to numerous cognitive functions, from perceptual to attentional and decisional processes. However, the same functions have also been attributed to the frontal cortex. We previously conducted a series of reversible inactivations of the lateral intraparietal area (LIP) and of the frontal eye field (FEF) in the monkey which showed impairments in covert visual search performance, characterized mainly by an increase in the mean reaction time (RT) necessary to detect a contralesional target. Only subtle differences were observed between the inactivation effects in both areas. In particular, the magnitude of the deficit was dependant of search task difficulty for LIP, but not for FEF. In the present study, we re-examine these data in order to try to dissociate the specific involvement of these two regions, by considering the entire RT distribution instead of mean RT. We use the LATER model to help us interpret the effects of the inactivations with regard to information accumulation rate and decision processes. We show that: 1) different search strategies can be used by monkeys to perform visual search, either by processing the visual scene in parallel, or by combining parallel and serial processes; 2) LIP and FEF inactivations have very different effects on the RT distributions in the two monkeys. Although our results are not conclusive with regards to the exact functional mechanisms affected by the inactivations, the effects we observe on RT distributions could be accounted by an involvement of LIP in saliency representation or decision-making, and an involvement of FEF in attentional shifts and perception. Finally, we observe that the use of the LATER model is limited in the context of a visual search as it cannot fit all the behavioural strategies encountered. We propose that the diversity in search strategies observed in our monkeys also exists in individual human subjects and should be considered in future experiments